Optimizing the Capital Structure of Acquiring Banks in Nigeria through Merger and Acquisition Schemes - Fajuyagbe, Bamikole Samson (Journal of Danubian Studies and Research, 2023)
This study examined whether or not merger and acquisition schemes can optimize the capital structure of acquiring listed banks in Nigeria. The research used secondary source of data gathered from the financial statements of the banks. The study focused on banks industry and covered nineteen (19) )years from 2004 to 2022 to select ten (10) banks out of total population of fifteen (15) acquiring banks based on the available data using targeted sampling technique. The data collected were analyzed using multiple regression model of fixed effect, random effect and poled ordinary least squares. Finding from the research disclosed that the coefficient of financial synergy (0.0487) is positive and has a significant effect (p=0.3612>0.05) in optimizing the banks’ capital structure; while the beta value of realized profit (−1.962) is negative and insignificant effect (p=0.0001<0.05) in optimizing the capital structure of the acquiring banks in Nigeria. The study concluded that gaining more financial synergy through the merger and acquisition schemes will optimize the capital structures of the acquiring banks, while any profit on realization through the business combination may not optimize the capital structures of the acquiring banks in Nigeria.